Indonesia’s Presidential Election 2019 – The Big Battle for Java : Key in Struggle for Power - Lanti, Irman G. (2019)
Indonesia has just concluded the third direct presidential election in the country’s history. Exit polls projected Jokowi’s victory with an increased proportion of votes compared to 2014. Central to this victory were Central and East Java where Jokowi enjoyed a huge jump in vote proportion despite Prabowo making inroads in other provinces. Interestingly, this year’s election mirrored the first Indonesian election in 1955.